A discomfort threshold for impulsive whole-body vibration on a slamming-prone vessel. (May 2023) - Engelbrecht, Martinique; Bekker, Anriëtte
Abstract: This study contributes towards a threshold for the onset of discomfort stemming from vibration that is transmitted to the human body by means of impulsive wave slamming in dynamic shipping environments. Wave slamming is a random, violent, non-linear event. Subjective and objective data were collected from two research voyages on a slamming-prone vessel. Full-scale vertical acceleration measurements were conducted near work and accommodation areas on the vessel. A daily diary survey was used to gather human responses among passengers. In addition, instantaneous slamming vibration comfort ratings were obtained by observers on the ship Bridge during a test sequence that purposefully induced slamming. The results indicate that two different approaches converged to the same VD V 1hr comfort threshold (0.41 m / s 1.75 and 0.43 m / s 1.75 ), which corresponds to the limit where 50% of respondents indicated discomfort. A similar analysis using the r . m . s . metric converged to an identical threshold (0.03 m / s 2 ), irrespective of the accumulated time of assessment. Highlights: A WBV discomfort threshold was determined in a dynamic shipping environment. Two of the three techniques applied, converged to the same 1-hour VDV threshold. Irrespective of the period, all r.m.s. thresholds were the same. The r.m.s. threshold is three times that of the likely perception threshold. The 1-hour VDV threshold is similar to VDV criteria as reported in literature.